Descriptive study of various bacterial flora in chronic otitis media - Dixith, Rohan M.; Mahajan, Gundappa D.; Mukhtar, Sabreena; Prasad, Shubhangi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media (COM) is the inflammation of the middle ear, which is characterised by ear discharge due to tympanic membrane perforation, at least for over a month. The inflammation is due to the underlying infection, due to which the middle ear mucosa gets inflamed, leading to discharge and eventual perforation of the tympanic membrane. The aim of the study was to study the microbial flora and its culture and sensitivity from ear discharge in chronic otitis media. Methods: Total of 100 ears with either mucosal COM or squamosal COM were included in this study. Patients coming to the outpatient department (OPD) with discharging ear were subjected to aural suctioning/cleaning with the use of bulls eye lamp. After cleaning the external auditory canal, sterile aural speculum were introduced into the EAC, creating a sterile conduit. Following this, middle ear discharge or the discharge around the tympanic membrane was collected using sterile cotton swabs and sent for laboratory within half an hour for mycological and bacteriological study. Results: Majority of patients were in an age group of 10-20 years, followed by age group of 21-30 years. The male to female ratio was 4.7:5.3. Out of the 100 swabs sent for culture and sensitivity, 6 swabs had no growth whereas Pseudomonas aeroginosa was the highest isolated organism (36 swabs), followed by Proteus mirabilis (23 swabs). Aerobic infection was the commonest, isolated in 47.9% of culture positive swabs. Polymyxin B was the most sensitive antibiotic, whereas cefotaxime was the most resistant antibiotic. Conclusions: Pseudomonas aeruginosa and Proteus mirabilis are the main bacteria isolated in mucosal COM. There is development of drug resistance in the majority of bacteria in chronic otitis media, due to excessive usage of antibiotics, making the treatment much difficult.